2020
DOI: 10.3390/nu12051487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prebiotic and Probiotic Supplementation on Lactase Deficiency and Lactose Intolerance: A Systematic Review of Controlled Trials

Abstract: Lactose intolerance (LI) is characterized by the presence of primarily gastrointestinal clinical signs resulting from colonic fermentation of lactose, the absorption of which is impaired due to a deficiency in the lactase enzyme. These clinical signs can be modified by several factors, including lactose dose, residual lactase expression, concurrent ingestion of other dietary components, gut-transit time, and enteric microbiome composition. In many of individuals with lactose malabsorption, clinical signs may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 59 publications
0
40
0
3
Order By: Relevance
“…Based on the fact that intestinal microbiota can be modulated by supplementation, many studies have tried to induce a "healthy" microbiota in LNP subjects, in order to alleviate the signs and symptoms of lactose intolerance. As a result, a positive relationship has been found between probiotics and lactose intolerance, in relation to specific strains and concentrations [105]. Taking all this into consideration, diet-induced particularities in human microbiota could be an additional explanation for those discrepancies encountered in LP/LNP phenotypes and discussed in the present review.…”
Section: Lactose Intolerance and Intestinal Microbiotamentioning
confidence: 74%
See 1 more Smart Citation
“…Based on the fact that intestinal microbiota can be modulated by supplementation, many studies have tried to induce a "healthy" microbiota in LNP subjects, in order to alleviate the signs and symptoms of lactose intolerance. As a result, a positive relationship has been found between probiotics and lactose intolerance, in relation to specific strains and concentrations [105]. Taking all this into consideration, diet-induced particularities in human microbiota could be an additional explanation for those discrepancies encountered in LP/LNP phenotypes and discussed in the present review.…”
Section: Lactose Intolerance and Intestinal Microbiotamentioning
confidence: 74%
“…Another aspect of special relevance for the understanding of lactase phenotypes is the human microbiota, which has been described to elicit a direct influence on the appearance, or amelioration, of lactose intolerance clinical symptoms [104,105]. This relationship results from the ability of human colonic microbiota (the sum of all microorganisms present in the colon) and their genes (intestinal microbiome) to ferment undigested lactose.…”
Section: Lactose Intolerance and Intestinal Microbiotamentioning
confidence: 99%
“…Another aspect that can influence symptoms is the microbiota, as higher levels of Bifidobacterium species have been reported in CC versus TT or CT genotypes in European populations, a difference explained by the greater abundance of lactose available for bacterial fermentation in CC individuals due to lactose malabsorption [ 43 ]. Furthermore, probiotic supplementation in lactose-intolerant individuals has beneficial effects on HBT results and on symptoms of lactose intolerance [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Interestingly, studies have revealed that the use of intestinal probiotics can significantly reduce the incidence of neonatal NEC and severity of NEC, shorten the duration of the disease, and effectively reduce its mortality. 2,6 Thus, it is widely believed that the gastrointestinal flora and anomalous colonization of pathogenic bacteria are closely related to the incidence of NEC. 7 In recent years, it has been widely agreed that the diversity and dynamics of the intestinal microflora are altered in neonatal NEC, which is consistent with our research.…”
Section: Discussionmentioning
confidence: 99%